Before Copernicus and Copernicus - Vesel, Matjaž (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2020)
A discussion of Before Copernicus: The Cultures and Contexts of Scientific Learning in the Fifteenth Century edited by Rivka Feldhay and F. Jamil Ragep.